OPTIMIZATION OF TITANIUM NITRIDE FILM SYNTHESIS: CORRELATIONS BETWEEN THE STRUCTURE / MICRO-HARDNESS AND DEPOSITION CONDITIONS - POP, Mariana; NEGREA, G.; POP, A. (Studia Universitatis Babeș-Bolyai Physica, 2018)
The DC sputtering method based on the variation of the potential of target function of nitrogen flow rate, for the deposition of titanium nitride (TiN) films, with the elementary chemical composition close to the stoichiometric one is presented. The process control method used in these experiments is the identification of the nitrogen flow required for the deposition of stoichiometric TiN layers by using the target potential as the reference parameter. The effects of the nitrogen flow, polarization voltage and discharge current on the structure, microstructure and micro-hardness of TiN films was studied.